Indeks kesejahteraan spiritual Islam dalam kalangan remaja - Ab. Rahim, Sakinah (2019)
Measurement of spiritual aspect is vital in human psychology research. However, most of spirituality measurements were developed according to Western perspective. Thus, this study aimed to develop an instrument to measure the level of spiritual well-being among teenagers from Islamic perspective named Indeks Kesejahteraan Spiritual Islam Remaja (IKSIR). This study applied mixed-method design of qualitative and quantitative. The qualitative method was applied in the instrument development phase. The concept and constructs of IKSIR were developed based on Muslim scholars? ideas of Imam al-Ghazali?s masterpiece, Ihya? Ulumuddin as main reference; while the items are generated from the Quranic verses. IKSIR was endorsed by a panel of experts comprising of four lecturers in Islamic psychology and counseling, aqidah and philosophy, also testing and measurement. The data were collected through Delphi Technique and analyzed using Kappa coefficient test. Meanwhile, the quantitative method was applied in validation phase of IKSIR involving teenagers aged 16 as population. The instrument was administered in pilot study involving 37 teenagers as respondents to assess the degree of reliability and validity. Data were analyzed using Statistical Package for Social Science (SPSS) version 20.0 and Winsteps version 3.72.3. Analyzed data from pilot studies showed that the degree of reliability and validity of IKSIR is good with 10 items omitted because they do not fit with the measurement model?s standardization. Then, the instrument was administered in a survey engaging 298 teenagers. The result of the survey showed that the degree of reliability and validity of IKSIR is good. IKSIR showed unidimensional property with 10 problematic items; where five of them were gender biased. Five items were omitted, leaving the final version consisting 66 items. Meanwhile, the analysis on respondents? level of spiritual well-being found 13 respondents in excellent level; 180 in very good level while the rest 105 in good level. The analysis also showed respondents had high level of faith, knowledge, worship. However, four sub constructs of morals are at moderate level which are trusty, shyness, reliable speaks and braveness. As a conclusion, this study has successfully developed IKSIR. The findings can be used as a guideline for schools and Ministry of Education in drafting teenagers? development programs parallel to the National Philosophy of Education.